2020
DOI: 10.3390/sym12050857
|View full text |Cite
|
Sign up to set email alerts
|

Application of Six Sigma Model on Efficient Use of Vehicle Fleet

Abstract: Each business faces large competition in the market, and it is necessary to adopt the most effective methodology as possible in order to obtain the best solution. Six Sigma (6σ) is a set of techniques and tools for process improvement. The tools of Six Sigma apply within a simple improvement model known as Define–Measure–Analyze–Improve–Control (DMAIC). This paper shows that implementing Six Sigma can be more effective in managing the vehicle fleet. The combination of mathematical, i.e., statistical basis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…Analyzing the data in Table 1 and the four graphs in Figure 8, it was found that, for these reduced values of the step, relatively small different values were obtained, which means that at this level of detail the errors of the method are acceptable, and, therefore, the results obtained for the smallest step (0.01) will be used for interpretation (Figure 9). It is obvious that the results obtained are significantly different from the value of 3400 PPB, which is accepted by most authors [15,23,24,[27][28][29] or disputed by other authors [11][12][13] who do not propose another solution.…”
Section: 𝜎 = √mentioning
confidence: 83%
See 1 more Smart Citation
“…Analyzing the data in Table 1 and the four graphs in Figure 8, it was found that, for these reduced values of the step, relatively small different values were obtained, which means that at this level of detail the errors of the method are acceptable, and, therefore, the results obtained for the smallest step (0.01) will be used for interpretation (Figure 9). It is obvious that the results obtained are significantly different from the value of 3400 PPB, which is accepted by most authors [15,23,24,[27][28][29] or disputed by other authors [11][12][13] who do not propose another solution.…”
Section: 𝜎 = √mentioning
confidence: 83%
“…Since most works dedicated to the Six Sigma concept associate this concept with a maximum shift of 1.5σ and a long-term performance of 3.4 PPM or 3400 PPB [23,24,[27][28][29], it is obvious that this is only a short-term situation (although it is extreme-for the maximum drift), and the following question arises: For a 6σ process (which keeps its standard deviation value unchanged over time, but which naturally has a drift over time, remaining stable), what is the proportion of long-term non-conformities (long-term performance of 6σ processes)?…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian terdahulu mengenai quality improvement dan menurunkan cost of quality sudah dilakukan oleh beberapa peneliti. Penelitian dengan pendekatan DMAIC pada sektor seperti industri manufaktur (Daniyan et al, 2022;Guleria et al, 2021;Nandakumar et al, 2020;Ranade et al, 2021;Smętkowska & Mrugalska, 2018;Srinivasan et al, 2014), industri makanan (Henny et al, 2019), industri transportasi (Kucuk & Orbak, 2011;Kuvvetli & Firuzan, 2019;Nedeliaková et al, 2019;Stanivuk et al, 2020), dan industri kecil menengah (Abbes et al, 2018;Kharub et al, 2022). Dari penelitian tersebut, terdapat beberapa yang berfokus pada bidang transportasi dalam hal untuk meningkatkan kepuasan pelanggan baik secara langsung maupun tidak langsung.…”
Section: Gambar 1 Jumlah Penumpang Kereta Api Indonesiaunclassified
“…Meningkatnya pengguna kereta api menjadi salah satu faktor bahwa part dari kereta api yang dibuat oleh perusahaan manufaktur kereta api harus memiliki kualitas yang baik dan dapat memasok demand yang ada (Nedeliaková et al, 2019). Selain itu, penerapan DMAIC di sektor transportasi juga dapat digunakan untuk meminimalisir kecelakaan pada bus (Kuvvetli & Firuzan, 2019) dan menurunkan biaya logistik untuk meningkatkan kepuasan pelanggan (Kucuk & Orbak, 2011) maupun untuk pemilihan moda transportasi (Stanivuk et al, 2020).…”
Section: Gambar 1 Jumlah Penumpang Kereta Api Indonesiaunclassified
“…The studies about 6σ are classified within the framework of descriptive, experimental, conceptual and literature review (Nonthaleerak & Hendry, 2006;Ninerola, Rebull & Lara, 2021). The method is described in the literature on the manufacturing sector (Koch, Yang, & Gu, 2004;Erdiller & Orbak, 2005;Hsu, Pearn, & Wu, 2008;Boangmanalu, Abigail, Sembiring, & Tampubolon, 2020;Sithole & Nyembwe, 2020;Rebull, et al, 2020) and service sector (Dakhil, 2019;Stanivuk, et al, 2020;Abid, et al, 2020;Ali, 2020) applications; in the context of its relationship with Total Quality Management (TQM) (Yang, 2004;Çalışkan, 2006;Bircan & Köse, 2012;Elmacı, Uslu, & Tutkavul, 2013) and lean (Edgeman & Bigio, 2004;Turan & Turan, 2019;Ikumapayi, et al, 2020;Gholami, et al, 2021;Costa, et al, 2021); it is also seen that it is the subject in conceptual and descriptive frameworks (Pyzdek, 2000;Rasis, Gitlow, & Popovic, 2002;Rowlands, 2003;Coronado & Antony, 2004;Antony, 2004;Ülgen, 2014;Uluskan, 2017). According to Kwalk & Anbari (2006) 6σ includes the combination of five methods; TQM or continuous quality improvement, customer focus, multiple analysis methods, financial performance and project management (Lee & Chang, 2012, p.453).…”
Section: Introductionmentioning
confidence: 99%